Group Work of Communicative Language Teaching Approach for Boosting Speaking Interactive Purposes - Susanti, Susanti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to enhance learners’ speaking competence, as they have experienced various hindrances in acquiring speaking skill during English course. These hindrances include passive classroom environments, uninterested lessons, a lack of interaction, the dominance of the mother tongue over the target language, and other related issues. They found speaking to be challenging, especially for transactional and interpersonal purposes in their English course. As a consequence, the speaking class did not run smoothly. The target participants of this study were 2nd semester students from Technique Informative program at STMIK Pontianak in the Academic year 2024/2025, consisting of thirty students with varying levels of English proficiency. Classroom action research was the research design applied by the researcher, using group work as one of the Communicative language teaching (CLT) approach to assist learners overcoming their speaking difficulties. This study employed both qualitative and quantitative methods. It consisted of two cycles, with three meetings in each cycle. Then, the observation list and speaking tests were used as research instruments to gain data, which were then analyzed using Simple Regression in SPSS ver.25. The outcome clearly proves that group work within the Communicative Language Teaching (CLT) approach significantly boosts learners’ speaking expertise, especially in using interactive language for transactional (delivering information) and interpersonal purposes (maintaining social connection) among learners during communication in the teaching and learning process, both inside and outside the classroom. This improvement is supported by observational data which show a shift in classroom dynamics—from teacher dominance in the first cycle to reduced teacher control and increased student interaction and participation in the second cycle, along with improved students’ speaking performance and also proved from the ANOVA table F is 26.852, sig. 0.00, means there is significant influence of group work of CLT approach in enhancing interactive purposes of learners’ speaking skill of target language